Climate security observatory Zambia: Summary for policymakers - CGIAR FOCUS Climate Security (2023)
Zambia has historically qualified as a regional model of stability and peace. However, this status is being undermined by a number of socio-political factors, including deeply entrenched patterns of social inequality and gender discrimination, high levels of poverty and youth unemployment, as well as recurring episode of electoral violence. Climate and extreme weather events compound most of these vulnerabilities and even create new ones. This profile, derived from the Climate Security Observatory, answers: 1) HOW does climate worsen the root causes of conflict? 2) WHERE are the most vulnerable areas to climate induced insecurities and risks? 3) WHO are the vulnerable groups to climate and security risks that should be targeted? and 4) WHAT needs to be done to break the cycle between climate and conflict?